Mainstream TV and social representations: Netflix and the Rosa Peral case - Lando, Arturo (Revista de Estudios Socioeducativos. ReSed, 2024)
This work aims to show how two Netflix audio-visual contents, Burning Body and Rosa Peral’s Tapes, are perfect examples of the functioning of contemporary mainstream narratives. The term mainstream refers to the set of media content constructed to maximize the audience. These two productions narrate the story of Barcelona “Urban Guard Crime” (2017-2020), respectively, using the language of a fictional TV series and a true-crime documentary. Based on the criterion of audience maximization, both products show that the social representations staged by contemporary entertainment narratives need to be based on transgressive, unpleasant, and disturbing elements, even if they seemingly intend to present themselves as moral tales. In other words, mainstreaming needs relevant non-mainstream elements to thrive.